2022
DOI: 10.3389/fnmol.2022.857293
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Volume and Plasma Brain-Derived Neurotrophic Factor Levels in Patients With Depression and Healthy Controls

Abstract: The aim of the present study was to investigate associations between hippocampal subfield volumes and plasma levels of brain-derived neurotrophic factor (BDNF) in patients experiencing a first episode of major depression (MD) (n = 30) as compared to healthy controls (HC) (n = 49). Covariate-adjusted linear regression was performed to compare the MD and healthy groups, adjusting for age, sex, and total estimated intracranial volume. We demonstrated that there were no differences in total hippocampal volume betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…We also ensured that no HC had a history of serious medical and neurological diseases or a family history of major psychiatric or neurological diseases among their first-degree relatives. Although our study population overlaps in part with several of our previously published studies (39,40), no study has analyzed the correlation between cortical gyrification, plasma BDNF levels, and psychiatric symptoms.…”
Section: Participantsmentioning
confidence: 99%
“…We also ensured that no HC had a history of serious medical and neurological diseases or a family history of major psychiatric or neurological diseases among their first-degree relatives. Although our study population overlaps in part with several of our previously published studies (39,40), no study has analyzed the correlation between cortical gyrification, plasma BDNF levels, and psychiatric symptoms.…”
Section: Participantsmentioning
confidence: 99%
“…The hippocampus is linked to the pathogenesis of depression, and numerous studies have confirmed its morphological changes. 13,14 This study found that the volumes of the left CA4, left GC-ML-DG, and right presubiculum were significantly decreased in MDD group, and the glutamate concentration was associated with the hippocampal volume. Glutamate homeostasis is seen to be an important component of mood disorder neurobiology, and the glutamate-glutamine cycle plays an important role in glutamate homeostasis in the central nervous system (CNS).…”
Section: Discussionmentioning
confidence: 70%
“…Many studies have confirmed that patients with depression have reduced overall and subregional hippocampal volumes compared with those in the control group. [13][14][15] Overall, hippocampal volume loss is a recognized neuroimaging finding in patients with MDD, but its significance and etiology remain unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given that recent studies have shown alterations in emerging biomarkers such as brain derived neurotrophic factor and neurofilament light chain (axonal damage) that reflect possible pathophysiologies involved in mood disorders [52,53], measuring the potential effects of nutraceuticals on these biomarkers may provide vital mechanistic information. A recent review has postulated the involvement of nutritional interventions in altering BDNF concentrations [54].…”
Section: Andandmentioning
confidence: 99%